Privacy Policy Pop-up: A Genre Analysis of Journal Websites’ HTTP Cookies - Lendik, Lisbeth Sinan (Journal of Modern Languages, 2023)
Online users are made to believe that they have control over their data privacy through the selection of website cookie options. Due to transparency requirements, policies to protect online users focus on giving them more control over their data privacy. This study examines how transparency is communicated through HTTP cookies found on academic journal websites. The analysis aims to uncover the communicative practice of this web-mediated disclosure genre through the rhetorical moves and linguistic features presented in the statements. A total of ten HTTP cookies from online journals are gathered based on random selection for this analysis. The findings revealed four obligatory moves and seven optional steps. The study also finds the use of active voice, action verbs, and self-reference pronouns to be common in the statements to realise the rhetorical function of transparency in HTTP cookies. A consistent genre pattern can be seen throughout the websites which shows the adherence to regulatory requirements while maintaining unique ways of presenting the HTTP cookies.